Teacher Resilience and Well-Being: Navigating Burnout in the Era of Educational Digitalization - Nur Ela, Nur Ela (Worldwide Research Publishing, 2025)
The rapid digitalization of education has brought significant changes in the dynamics of teaching, offering both opportunities and challenges. In the midst of this transformation, the resilience and well-being of teachers is a crucial factor in preventing professional burnout. The increasing use of digital platforms in teaching exacerbates stressors, which can affect teachers' mental health and job satisfaction. This phenomenon, often referred to as